Teacher Support as Determinant of Academic Achievement - Sharma, Dr. Gouri (IJRDO- Journal of Educational Research, 2016)
Measuring achievement is a major part of the learning process and informs educators of student talent andprogress toward educational goals. Today’s modern society expects each one to be a high achiever. It has become anindicator of a child’s future. Parents, teachers and higher authorities concerned with effective academic performanceof the students. Present study aimed to investigate the effect of teacher support locale and sex on academicachievement. For this purpose initially larger number of student Studying in government schools of Rajnandgaondistrict of Chhattisgarh state were selected out of which 646 students were retained as final sample. To measure theacademic achievement of the student, over all marks obtained by the student in different subjects (viz-Hindi,English, Mathematics, Science, & Social Science) in class 10th board examination was used. The dependent variableof the study was academic achievement and independent variables were teacher support locale and sex. To analyzethe data descriptive statistics, and ANOVA technique is used. The ANOVA analysis reveals that teacher support andlocale affect independently as well as jointly to academic achievement whereas role of sex was not found to besignificant.